Quantification of total and visceral adipose tissue in fructose‐fed rats using water‐fat separated single echo MRI. (21st May 2013) - Rönn, Monika; Lind, P. Monica; Karlsson, Helen; Cvek, Katarina; Berglund, Johan; Malmberg, Filip; Örberg, Jan; Lind, Lars; Ortiz‐Nieto, Francisco; Kullberg, Joel
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to setup a rodent model for modest weight gain and an MRI‐based quantification of body composition on a clinical 1.5 T MRI system for studies of obesity and environmental factors and their possible association. Design and Methods Twenty‐four 4‐week‐old female Fischer rats were divided into two groups: one exposed group (n = 12) and one control group (n = 12). The exposed group was given drinking water containing fructose (5% for 7 weeks, then 20% for 3 weeks). The control group was given tap water. Before sacrifice, whole body MRI was performed to determine volumes of total and visceral adipose tissue and lean tissue. MRI was performed using a clinical 1.5 T system and a chemical shift based technique for separation of water and fat signal from a rapid single echo acquisition. Fat signal fraction was used to separate adipose and lean tissue. Visceral adipose tissue volume was quantified using semiautomated segmentation. After sacrifice, a perirenal fat pad and the liver were dissected and weighed. Plasma proteins were analyzed by Western blot. Results The weight gain was 5.2% greater in rats exposed to fructose than in controls (P = 0.042). Total and visceral adipose tissue volumes were 5.2 cm3 (P = 0.017) and 3.1 cm3 (P = 0.019) greater, respectively, while lean tissue volumes did not differ. The level of triglycerides and apolipoprotein A‐I was higher (P = 0.034, P = 0.005, respectively) in fructose‐exposed rats. Conclusions The setup induced and assessed a modest visceral obesity and hypertriglyceridemia, making it suitable for further studies of a possible association between environmental factors and obesity.